Posttraumatic intracranial migration of silicone oil after treatment of retinal detachment, a rare complication - Abhinaya Aroll, MD; Austin Campbell, MD; Alan V Krauthamer, MD; Leszek Pisinski, MD (Radiology Case Reports)
Retinal detachment is popularly treated with intraocular silicone oil tamponade. A rarely observed complication of this procedure is intracranial migration of silicone oil through the optic canal. Though this is typically a benign finding, it can be mistaken on imaging for intracerebral hemorrhage or neoplasm. Orbital trauma has previously been described to have an association with cases of silicone oil migration. Here we present a case of a patient who endured facial trauma, including orbital fracture, and was found to have intraocular silicone oil brain migration. CT imaging of the head revealed hyperdense oil tracking along the optic nerve and settling in the suprasellar cistern and right lateral ventricle.